Immunometabolic Analysis of Mobiluncus mulieris and Eggerthella sp. Reveals Novel Insights Into Their Pathogenic Contributions to the Hallmarks of Bacterial Vaginosis - McKenzie, Ross; Maarsingh, Jason D.; Łaniewski, Paweł; Herbst-Kralovetz, Melissa M. (Frontiers in Cellular and Infection Microbiology, 2021)
The cervicovaginal microbiome plays an important role in protecting women from dysbiosis and infection caused by pathogenic microorganisms. In healthy reproductive-age women the cervicovaginal microbiome is predominantly colonized by protective Lactobacillus spp. The loss of these protective bacteria leads to colonization of the cervicovaginal microenvironment by pathogenic microorganisms resulting in dysbiosis and bacterial vaginosis (BV). Mobiluncus mulieris and Eggerthella sp. are two of the many anaerobes that can contribute to BV, a condition associated with multiple adverse obstetric and gynecological outcomes. M. mulieris has been linked to high Nugent scores (relating to BV morphotypes) and preterm birth (PTB), whilst some bacterial members of the Eggerthellaceae family are highly prevalent in BV, and identified in 85-95% of cases. The functional impact of M. mulieris and Eggerthella sp. in BV is still poorly understood. To determine the individual immunometabolic contributions of Eggerthella sp. and M. mulieris within the cervicovaginal microenvironment, we utilized our well-characterized human three-dimensional (3-D) cervical epithelial cell model in combination with multiplex immunoassays and global untargeted metabolomics approaches to identify key immune mediators and metabolites related to M. mulieris and Eggerthella sp. infections. We found that infection with M. mulieris significantly elevated multiple proinflammatory markers (IL-6, IL-8, TNF-α and MCP-1) and altered metabolites related to energy metabolism (nicotinamide and succinate) and oxidative stress (cysteinylglycine, cysteinylglycine disulfide and 2-hydroxygluatrate). Eggerthella sp. infection significantly elevated multiple sphingolipids and glycerolipids related to epithelial barrier function, and biogenic amines (putrescine and cadaverine) associated with elevated vaginal pH, vaginal amine odor and vaginal discharge. Our study elucidated that M. mulieris elevated multiple proinflammatory markers relating to PTB and STI acquisition, as well as altered energy metabolism and oxidative stress, whilst Eggerthella sp. upregulated multiple biogenic amines associated with the clinical diagnostic criteria of BV. Future studies are needed to evaluate how these bacteria interact with other BV-associated bacteria within the cervicovaginal microenvironment.